On the new hyperbolic wave solutions to Wu-Zhang system models - Yazgan, Tugba; Ilhan, Esin; Celik, Ercan; Bulut, Hasan (Springer, 2022)
In this study, some solitary wave solutions of the Wu-Zhang system are analyzed using the modified expansion function method and the sine-Gordon expansion method. Solitary wave solutions of this non-linear mathematical model consisting of hyperbolic and trigonometric function structures are get. Two and three dimensional, density graphics of the solitary solutions of the mathematical models are drawn by choosing the appropriate parameters. It was seen that all solution functions found as a result provide the mathematical model. In this study, Wolfram Mathematica software program was used for all mathematical calculations.
Keywords: The sine-Gordon expansion method (SGEM); The modified expansion function method (MEFM); Wu-Zhang system